Moderation of effects of AAC based on setting and types of aided AAC on outcome variables: An aggregate study of single-case research with individuals with ASD. (June 2014) - Ganz, Jennifer B.; Rispoli, Mandy J.; Mason, Rose Ann; Hong, Ee Rea
<x xml:space="preserve">Abstract</x> Objective: The purpose of this meta-analysis was to evaluate the potential moderating effects of intervention setting and type of aided augmentative and alternative communication (AAC) on outcome variables for students with autism spectrum disorders. Methods: Improvement rate difference, an effect size measure, was used to calculate aggregate effects across 35 single-case research studies. Results: Results indicated that the largest effects for aided AAC were observed in general education settings. With respect to communication outcomes, both speech generating devices (SGDs) and the Picture Exchange Communication System (PECS) were associated with larger effects than other picture-based systems. With respect to challenging behaviour outcomes, SGDs produced larger effects than PECS. Conclusion: This aggregate study highlights the importance of considering intervention setting, choice of AAC system and target outcomes when designing and planning an aided AAC intervention.